Safety and efficacy of recombinant activated factor VII in nonhemophilia children with severe or life-threatening bleeding: a report from the SeveNBleeP registry - Blatný, Jan; Mathew, Prasad; Monagle, Paul; Ovesna, Petra; Fiamoli, Veronika (Blood coagulation & fibrinolysis, 2014)
We evaluated efficacy and safety of recombinant activated factor VII (rFVIIa) in nonhemophilia children with life-threatening or severe bleeding. Using data from the SeveNBleeP registry, we analyzed demographic, clinical, laboratory, and treatment data for children who received rFVIIa to treat severe hemorrhage. The SeveNBleeP registry was international registry formed in 2005, to collect information on the use of rFVIIa in the off-label setting of severe bleeding in nonhemophilia patients. There were 191 patient records entered into this registry, of which 164 were validated. Of the 164 records, in 137 patient records, rFVIIa was used for treatment of bleeding episodes. Of these 137 treatment episodes, 42 were in neonates and infants under 1 year of age. Use of rFVIIa significantly improved laboratory parameters (prothrombin time, international normalized ratio, activated partial thromboplastin time, hematocrit), reduced estimated blood loss, and reduced requirements for blood products (packed red blood cells and fresh frozen plasma) in those more than 1 year of age. There was no significant reduction in requirements for blood products after rFVIIa administration in the neonates and infants, but there was a trend to lower frequency of FFP use after rFVIIa administration. There was one thromboembolic event in an infant that was related to administration of rFVIIa. No other serious adverse events were reported that were related to administration of rFVIIa. In nonhemophilia-associated bleeding in children, rFVIIa appears to be safe and efficacious in reducing estimated blood loss in children over 1 year of age, although its effectiveness in infants below 1 year of age was less clear.
Keywords: Registries; Hemorrhage; Infant; Humans; kojenec; dítě; registrace; Child; Female; faktor VIIa; Factor VIIa; lidé; Recombinant Proteins; předškolní dítě; rekombinantní proteiny; ženské pohlaví; Male; Retrospective Studies; Adolescent; krvácení; retrospektivní studie; mužské pohlaví; Child, Preschool; mladiství